2016
DOI: 10.1186/s12885-016-2961-2
|View full text |Cite
|
Sign up to set email alerts
|

HPV Prevalence in the Dutch cervical cancer screening population (DuSC study): HPV testing using automated HC2, cobas and Aptima workflows

Abstract: BackgroundPrimary high risk (hr)HPV screening will be introduced in The Netherlands in January 2017. Our aim was to determine the hrHPV prevalence in the Dutch cervical cancer screening population (DuSC study).MethodsA total of 12,113 residual PreservCyt cervical samples from the Dutch population based cytology screening program were rendered anonymous, randomized and tested for hrHPV using 3 HPV assays on their respective automated platforms: QIAGEN’s digene® HC2 HPV DNA Test® (HC2, signal amplification), Roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
5
28
0
Order By: Relevance
“…Apart from these types 58, 31, 35 and 68 are more common than type 45. Meanwhile in another study from the Netherland, although HPV 16 was the most prevalent genotype amongst women with abnormal cervical cytology, most of the cases belonged to the non‐16, 18/45 group. In that study, the Aptima assay was one of the two assays used for HPV detection and genotyping.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Apart from these types 58, 31, 35 and 68 are more common than type 45. Meanwhile in another study from the Netherland, although HPV 16 was the most prevalent genotype amongst women with abnormal cervical cytology, most of the cases belonged to the non‐16, 18/45 group. In that study, the Aptima assay was one of the two assays used for HPV detection and genotyping.…”
Section: Discussionmentioning
confidence: 93%
“…In a previously published study, it was seen that amongst women residing in Kuwait, with epithelial abnormalities in cervical smears cytology, the HPV type 16 is the most common genotype . Similarly in another recent large population based study from the Netherlands, HPV 16 was found to be the most common HPV genotype amongst women with cervical smear abnormalities . However, in both these studies, although HPV 16 was the most common genotype, most of the high risk HPVs belonged to genotypes other than types 16 and 18.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recently, a number of studies have also evaluated the clinical performance of the Cobas 4800 HPV test, the Aptima HPV assay, and HC2 in population‐based primary cervical screening setting …”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Recently, a number of studies have also evaluated the clinical performance of the Cobas 4800 HPV test, the Aptima HPV assay, and HC2 in population-based primary cervical screening setting. [25][26][27] In Ireland, the National Cervical Screening Program CervicalCheck offers cytology-based screening to all women aged 25-60 y. Since May 2015, CervicalCheck has incorporated HPV testing for the triage of women with minor abnormalities and both the Cobas 4800 HPV test and the Aptima HPV assay are being employed.…”
Section: Introductionmentioning
confidence: 99%